2014
DOI: 10.1117/12.2056131
|View full text |Cite
|
Sign up to set email alerts
|

Towards a reliability assessment of the C2Nand wind speed vertical profiles retrieved from GeMS

Abstract: The advent of a new generation of Adaptive Optics systems called Wide Field AO (WFAO) mark the beginning of a new era. By using multiple Guide Stars (GSs), either Laser Guide Stars (LGSs) or Natural Guide Stars (NGSs), WFAO significantly increases the field of view of the AO-corrected images, and the fraction of the sky that can benefit from such correction. Different typologies of WFAO have been studied over the past years. They all require multiple GSs to perform a tomographic analysis of the atmospheric tur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…GeMS is the first laser assisted MCAO system running on sky and this study proves, for the first time, that the SLO-DAR technique method for the wind estimate with multiple sources provides reliable results as in agreement with an independent reference previously validated. Besides that, the development of other WFAO systems is in progress for the 8-10 m class telescopes (among these we remind AOF 5 at For completeness we observe that in a couple of papers (Neichel et al 2014b;Masciadri et al 2016) some preliminary results of these study have been published. In the first one just some preliminary WS comparisons on a very small number of nights has been presented.…”
Section: Discussionmentioning
confidence: 98%
“…GeMS is the first laser assisted MCAO system running on sky and this study proves, for the first time, that the SLO-DAR technique method for the wind estimate with multiple sources provides reliable results as in agreement with an independent reference previously validated. Besides that, the development of other WFAO systems is in progress for the 8-10 m class telescopes (among these we remind AOF 5 at For completeness we observe that in a couple of papers (Neichel et al 2014b;Masciadri et al 2016) some preliminary results of these study have been published. In the first one just some preliminary WS comparisons on a very small number of nights has been presented.…”
Section: Discussionmentioning
confidence: 98%
“…We used the same model configuration used in Neichel et al [ 2 ] with three domains in grid-nesting configuration having resolution of 10 km, 2.5km and 0.5 km. We simulated 43 nights for which GeMS telemetry data were available.…”
Section: Wind Speed Profiles From the Atmospherical Meso-scale Model mentioning
confidence: 99%
“…In this contribution we performs the comparison between wind speed measured by GeMS and reconstructed by the atmospherical model at mesoscale Meso-Nh on a rich statistical sample of 43 nights with the goal to provide a more complete analysis with respect to Neichel et al 2014 [ 2 ] and we present preliminary results related to the wind direction. In a previous study, indeed, Masciadri et al, 2013Masciadri et al, , 2015 ] showed that the non-hydrostatical mesoscale atmospherical model Meso-Nh was able to provide reliable wind speed and direction profiles on the whole troposphere and stratosphere (up to 20-25 km) above top-level astronomical sites.…”
Section: Introductionmentioning
confidence: 99%
“…At present, profiling using AO instruments is performed from the cross-correlation of Wave-Front Sensor (WFS) measurements (Laidlaw et al 2018;Mazzoni et al 2016;Ono et al 2017;Martin et al 2016;Neichel et al 2014;Vidal et al 2010), with profile height limits of ∼ 10-20 km imposed principally by the telescope diameter, and then additionally the cone effect for laser-based AO (Foy 2000). However, such an approach is only available on multiple GSbased systems and can not be deployed to predict PSF variations on images delivered by single-conjugated AO systems.…”
Section: Introductionmentioning
confidence: 99%